Developing English Vocabulary Through The Busuu App - Tika Khairunnisa; Lidiyatul Izzah; Muhamad Sofian Hadi (Universitas Cokroaminoto Palopo, 2021)
The purpose of this study was to determine the improvement of English learning using the Busuu application. This study used a quantitative method and the design used in this quantitative method was pre-experimental using one group pre-test and post-test. The samples in this study were 31 students of class 10th Ipa SMA Al-Mukhlisin Ciseeng Bogor in the academic year 2019-2020. The mean value of the pre-test results was 43.39 and the post-test 89.19. The results of the t-test calculation can be concluded that the Busuu application has a significant effect on students' vocabulary skills. Evidenced by getting 1.345 for the Pre-test and 2.765 for Post-test. The means for the pre-test were 43.39 and 89.19 for the post-tests. The result of the t.calculation score of 12,492 was higher than the t.table score of 2,042 at the 5% significance level. This means that the Busuu application improves the vocabulary skills of grade X SMA Al-Mukhlisin students.